Riskbedömning av grundvattenförekomster i Floda - ALKEMARK, CLARA; AL ASFAR, IYAS; HAMMERLID, JAKOB; LJUNGSTRÖM, MÅNS; RINGDAHL, MATHILDA (My University, 2020)
This report seeks to make a risk assessment of the groundwater in the area around Floda, in the municipality of Lerum, Sweden. Water protection areas1 have for a long time been designed based on, for an example, the retention time of the groundwater and activities within the catchment area. To enable well designed water protection areas, a risk-based approach is needed considering the local conditions. Hence, a risk assessment is needed to help preserving the groundwater quality by adapting the water protection area to the risks in the area. The risk here is evaluated by identifying the vulnerability of the different parts of the analysed area, potential pollutant sources as well as the threat they pose to the water. Furthermore, this is combined with data on water flow direction and geological fracture zones. The vulnerability was estimated using the geological and hydrogeological properties of the area and the potential pollutant sources were identified through a field study. Based on these factors, a relative risk assessment score from 2 to 12 was estimated. It was identified that the two eskers in the area were at the largest risk of contamination. There is currently a water protection area covering parts of the northern esker. Recommendations about the size and delination of this water protection area are made based on the risk assessment. Since the water protection area only covers the south western part of the northern esker, it is recommended to extend the area to include the entire northern esker, to protect the possibility of future use of the groundwater. Additionally, there is another esker in the southern part of the area that is recommended to protect in form of a water protection area as well, due to additional pressures from climate change in the future. 1 Water protection area, or vattenskyddsområde in Swedish, is an area, established by a Swedish municipality or the county administration, in where land use and handling of chemical substances is regulated to protect the groundwater.
Keywords: Grundvattenskydd; vattenskyddsområde; sårbarhet; grundvattenförorening; riskbedömning